THE ROLE OF ART COMPONENTS IN IMPROVING UNDERSTANDING OF GEOMETRY AND ALGEBRA CONCEPTS: A SYSTEMATIC STEAM LEARNING APPROACH - Israwali Justan; Nur Amini Tawakkal; Arinil Hidayah (Prima: Jurnal Pendidikan Matematika, 2026)
Geometry and algebra learning remains a challenge for many students due to its abstract nature and the need for strong visualization and symbolic representation skills. The integration of art components into the STEAM approach offers a pedagogical solution that can bridge this gap through visual representation, creativity, and the construction of more concrete meaning. This research is a systematic literature review of 20 articles published between 2018 and 2025 that discuss the implementation of art elements in STEAM learning at various levels of education. The results show that art integration has a significant influence on improving the understanding of geometric concepts, including spatial abilities, visualization of shapes, shape recognition, and modern geometric modeling through artistic activities such as batik motif design, model construction, origami exploration, and the use of visual-based software such as GeoGebra and Surfer. In algebra, art helps strengthen the understanding of patterns, algebraic structures, function graphs, and the representation of variable relationships through a creative visual approach. In addition, art-based STEAM learning has been shown to improve students' creativity, motivation, visual literacy, learning outcomes, and problem-solving abilities in various cultural contexts and authentic projects. These findings confirm that the Art component serves not only as an aesthetic element but also as an effective cognitive tool in deepening conceptual understanding of mathematics. Therefore, art integration in STEAM is recommended as an innovative and relevant learning strategy in developing 21st-century competencies, particularly in geometry and algebra.Keywords: STEAM, Art Integration, Geometry, Algebra, Visualization, Creativity